PET/CT evaluation of response to chemotherapy in non-small cell lung cancer: PET response criteria in solid tumors (PERCIST) versus response evaluation criteria in solid tumors (RECIST) - Ding, Qiyong; Cheng, Xu; Yang, Lu; Zhang, Qingbo; Chen, Jianwei; Li, Tiannv; Shi, Haibin (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
Background: 18F-FDG PET/CT is increasingly used in evaluation of treatment response for patients with non-small cell lung cancer (NSCLC). There is a need for an accurate criterion to evaluate the effect and predict the prognosis. The aim of this study is to evaluate therapeutic response in NSCLC with comparing PET response criteria in solid tumors (PERCIST) to response evaluation criteria in solid tumors (RECIST) criteria on PET/CT. Methods: Forty-four NSCLC patients who received chemotherapy but no surgery were studied. Chemotherapeutic responses were evaluated using 18F-FDG PET and CT according to the RECIST and PERCIST methodologies. PET/CT scans were obtained before chemotherapy and after 2 or 4-6 cycles’ chemotherapy. The percentage changes of tumor longest diameters and standardized uptake value (SUV) (corrected for lean body mass, SUL) before and after treatment were compared using paired t-test. The response was categorized into 4 levels according to RECIST and PERCIST: CR (CMR) =1, PR (PMR) =2, SD (SMD) =3, PD (PMD) =4. Pearson chi-square test was used to compare the proportion of four levels in RECIST and PERCIST. Finally the relationship between progression-free survival (PFS) and clinicopathologic parameters (such as TNM staging, percentage changes in diameters and SUL, RECIST and PERCIST results etc.) were evaluated using univariate and multivariate Cox proportional hazards regression method. Results: The difference of percentage changes between diameters and SUL was not significant using paired t-test (t=–1.69, P=0.098). However the difference was statistically significant in the 40 cases without increasing SUL (t=–3.31, P=0.002). The difference of evaluation results between RECIST and PERCIST was not significant by chi-square test (χ2=5.008, P=0.171). If RECIST evaluation excluded the new lesions which could not be found or identified on CT images the difference between RECIST and PERCIST was significant (χ2=11.759, P=0.007). Reduction rate of SULpeak (%), RECIST and PERCIST results were significant factors in univariate Cox analysis. But Multivariate Cox proportional hazards regression analysis demonstrated that only PERCIST was a significant factor for predicting DFS [hazard ratio (HR), 3.20; 95% (CI), 1.85-5.54; P